ANALISIS MEDAN ELASTIS DI DALAM SETENGAH RUANG ISOTROPI MELINTAN G AKIBAT BEBAN NORMAL DI PERMUKAANNYA - IGN Wiratmaja Puja (Mesin, 1998)
This paper evaluate the elastic ï¬eld that induced by a uniform pressure applied over a circular area on the surface of an elastic half space. The half space is transversely isotropic, where the planes of isotropy are parallel to the surface. A potential function method is adopted where the elastic ï¬eld is written in terms of three harmonic functions. The known point force Green functions are used to ï¬nd the solution for uniform normal load over the area by quadrature. The elastic displacement and stress ï¬eld are evaluated in term of closed form expressions containing complete elliptic integrals of the ï¬rst, second and third kinds. Following limiting procedure allows the isotropic solution to be obtained. It is shown that the present results agree with the previous published solutions but the new solutions could be put in a more convenient form. Special consideration is also given to derive the limiting form of the stress ï¬eld on the surface.